Impact of access to capital and abiotic stress on production efficiency: Evidence from rice farming in Cambodia. (December 2018) - Mishra, Ashok K.; Bairagi, Subir; Velasco, Maria Lourdes; Mohanty, Samarendu
Highlights: Mean technical efficiency of rice farmers is about60%. Cambodian rice farmers can increase their production by about 40% with existing resources. Drought and soil fertility are major sources of inefficiency. Adoption of drought-tolerant varieties could help increase output and efficiency. Access to capital and education can significantly improve rice farming efficiency. Abstract: Cambodia is one of the climatic stress-prone countries in Southeast Asia. Rice is the dominant cash crop for Cambodians, and is adversely affected by recurrent droughts and floods. In addition, farmers have limited or no access to capital markets. This article investigates the impact of abiotic stresses (droughts and floods) and access to capital on the farming efficiency of smallholders in Cambodia. We find that the mean technical efficiency of rice farmers is about 0.60, implying that farmers can increase their production by about 40% with existing resources. Drought and soil fertility were identified as the major sources of inefficiency in rice production. Adoption of drought-tolerant varieties could help increase output and efficiency. We also find that access to capital and educational attainment significantly improved rice farming efficiency. Finally, we conclude that increasing rice productivity can help in improving income and thereby reducing poverty among Cambodian rice producers.